Prevalence and patterns of third molar impaction among Ethiopians in Addis Ababa: a retrospective pilot study - Tsedenia Gebeyehu; Yeshewas Abaynew (Scientific Reports, 2024)
Abstract Tooth impaction is a condition in which a tooth does not reach its normal position and is often observed in the third mandibular molar due to inadequate space. This study aimed to investigate the prevalence and configuration of the impacted third molars with an emphasis on angular orientations in a sample of the Ethiopian population. This cross-sectional study included a retrospective analysis of 291 patient records and orthopantomography data from the archives of a private dental clinic in Addis Ababa, during the study period from December 2020 to November 2022. Demographic details and data on the position and level of the impacted third molars were evaluated using the Winter classification. Data were analyzed for frequency distribution. The prevalence of impacted third molars was 22% (n = 64), with a greater incidence on the right side (60.9%) and a higher frequency in the mandible (67.2%). Vertical angulation (32.8%), followed by mesioangular angulation (31.2%), was the most common impaction pattern. The results highlight the need for improved treatment protocols for third molar impaction, emphasizing the prevalence in the mandible and the importance of addressing vertical impaction. Regular dental check-ups are essential for assessing third molar impaction and planning appropriate management. These data can inform policymaking and treatment considerations for impacted third molars in the Ethiopian population.